2019
DOI: 10.1177/0300060519847352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6-months of oral ferrous and ferric supplement therapy in patients who were hospitalized for decompensated chronic heart failure

Abstract: Objective Anemia is common in patients with chronic heart failure (CHF). This study aimed to examine the frequency of iron deficiency anemia in patients with CHF. We investigated the effects of oral ferrous or ferric supplementation on prognosis of CHF and quality of life. Methods A total of 201 patients with chronic decompensated heart failure were enrolled in a 6-month prospective study. Patients were randomly assigned to two groups. Patients in group I (n = 100) received ferrous fumarate and those in group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
0
15
1
1
Order By: Relevance
“…In terms of IV iron, FAIR-HF (p,0.001) [29] CONFIRM-HF (p,0.001) [31] and Toblli (p,0.01) [32] established improvement, however, Yeo et al concluded a negligible increase [34]. For oral iron supplements, Zdravkovic demonstrated increases from baseline in both oral arms (p,0.001) [28]. In contrast, Karavidas et al [26] and IRONOUT-HF [27] found no benefit.…”
Section: Iron Replacement For Aerobic Capacitymentioning
confidence: 97%
See 4 more Smart Citations
“…In terms of IV iron, FAIR-HF (p,0.001) [29] CONFIRM-HF (p,0.001) [31] and Toblli (p,0.01) [32] established improvement, however, Yeo et al concluded a negligible increase [34]. For oral iron supplements, Zdravkovic demonstrated increases from baseline in both oral arms (p,0.001) [28]. In contrast, Karavidas et al [26] and IRONOUT-HF [27] found no benefit.…”
Section: Iron Replacement For Aerobic Capacitymentioning
confidence: 97%
“…Iron Replacement for NYHA Classification and Health Related Quality of Life Measures Four (4) studies utilising oral iron replacement for HF patients with ID demonstrated mixed results in improving patient outcomes [25][26][27][28]. The KCCQ implemented in IRONOUT-HF and Karavidas et al drew conflicting conclusions of insignificant improvement in the IRONOUT-HF trial (p=0.57) [27], and significance by Karavidas et al (p=0.038) [26].…”
Section: The Association Between Iron Deficiency and Depressionmentioning
confidence: 99%
See 3 more Smart Citations